2005
DOI: 10.1007/s10265-005-0245-z
|View full text |Cite
|
Sign up to set email alerts
|

Selfing and inbreeding depression in seeds and seedlings of Neobalanocarpus heimii (Dipterocarpaceae)

Abstract: We evaluated the degree of selfing and inbreeding depression at the seed and seedling stages of a threatened tropical canopy tree, Neobalanocarpus heimii, using microsatellite markers. Selection resulted in an overall decrease in the level of surviving selfed progeny from seeds to established seedlings, indicating inbreeding depression during seedling establishment. Mean seed mass of selfed progeny was lower than that of outcrossed progeny. Since the smaller seeds suffered a fitness disadvantage at germination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 31 publications
6
70
1
2
Order By: Relevance
“…Seeds from one seed-tree (M3) even did not germinate. Loss of genetic diversity could be explained by a reduced fitness in seeds and seedlings leading to mortality, by instance through biparental inbreeding depression (Cheliak et al, 1985;Rajora et al, 2000;Hufford and Hamrick, 2003;Naito et al, 2005;Isagi et al, 2007;Duminil et al, 2009;Hasegawa et al, 2009). However, our data rather showed higher survival of offspring from related parents and fixation index showed excess of heterozygotes.…”
Section: Genetic Diversity Across Life-stagescontrasting
confidence: 59%
See 2 more Smart Citations
“…Seeds from one seed-tree (M3) even did not germinate. Loss of genetic diversity could be explained by a reduced fitness in seeds and seedlings leading to mortality, by instance through biparental inbreeding depression (Cheliak et al, 1985;Rajora et al, 2000;Hufford and Hamrick, 2003;Naito et al, 2005;Isagi et al, 2007;Duminil et al, 2009;Hasegawa et al, 2009). However, our data rather showed higher survival of offspring from related parents and fixation index showed excess of heterozygotes.…”
Section: Genetic Diversity Across Life-stagescontrasting
confidence: 59%
“…Loss of homozygote individuals seems indeed to be common in tree species (Cheliak et al, 1985;Hufford and Hamrick, 2003;Naito et al, 2005;Tamaki et al, 2009) and may result from very intensive competition for seedling establishment (Petit and Hampe, 2006) and heterozygote advantage (heterosis).…”
Section: Fixation Indexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the higher levels of selfing may explain the low observed heterozygosity at the edge. However, in general, selfing in tropical tree species produces inbreeding depression, causing the mortality of selfed seeds and individuals as was observed in Eucalyptus argutifolia (Kennington and James, 1997), Eucalyptus marginata (Millar et al, 2000), Pseudobombax munguba (Gribel and Gibbs, 2002), Platypodium elegans (Hufford and Hamrick, 2003) and Neobalanocarpus heimii (Naito et al, 2005). We observed significant higher germination in the SW than the edge, suggesting that inbreeding depression was higher in seeds from the edge, where selfing was highest.…”
Section: Genetic Diversity Inbreeding and Mating Systemsupporting
confidence: 55%
“…Interestingly, the review by Lowe et al, (2005) found all studies showed a significant impact of fragmentation on fitness, with reduction in outcrossing rates. Although fitness losses may be driven by mate limitation (Naito et al, 2005), the exact cause is unclear and may vary by species and landscape context. The implications and significance of such fitness losses will depend on the extent to which inbred material survives regeneration.…”
Section: Inbreeding Depressionmentioning
confidence: 99%